Qualitative Study Of Maintenance Of Wooden Structures Of Traditional Houses In Damp Environments - Zebua, Dermawan; Giawa, Jun Fajar Krisman (Innovative Research in Civil and Environmental Engineering, 2025)
The maintenance of wooden structures in traditional houses located in humid environments poses significant challenges due to the high risk of damage caused by moisture, fungal growth, and termite infestation. This study employs a qualitative approach to explore community maintenance practices, the challenges encountered, and the role of local wisdom in sustaining wooden traditional houses. Data were collected through in-depth interviews, participatory observation, and documentation at several traditional house sites in humid climate regions. The findings reveal that traditional maintenance methods, such as the use of natural preservatives, replacement of damaged components, and ventilation management, are effective in extending the lifespan of wooden structures. However, limited knowledge and resources remain major obstacles to preservation efforts. The integration of traditional techniques with modern technologies is expected to enhance maintenance effectiveness. This research provides strategic recommendations for the sustainable preservation of traditional houses and serves as a reference for the development of cultural heritage conservation policies in humid regions.